Comparative neuropathology of major Indian Bluetongue virus serotypes in a neonatal BALB/c mouse model - Anjaneya, A.; Singh, K.P.; Cherian, S.; Saminathan, M.; Singh, R.; Ramakrishnan, M.A.; Maan, S.; Maan, N.S.; Hemadri, D.; Rao, P.P.; Putty, K.; Krishnajyothi, Y.; et al. (2018)
Bluetongue virus (BTV) is neurotropic in nature, especially in ruminant fetuses and in-utero infection results in abortion and congenital brain malformations. The aim of the present study was to compare the neuropathogenicity of major Indian BTV serotypes 1, 2, 10, 16 and 23 by gross and histopathological lesions and virus distribution in experimentally infected neonatal BALB/c mice. Each BTV serotype (20 μl of inoculum containing 1 × 105 tissue culture infectious dose [TCID]50/ml of virus) was inoculated intracerebrally into 3-day-old mice, while a control group was inoculated with mock-infected cell culture medium. Infection with BTV serotypes 1, 2 and 23 led to 65–70% mortality at 7–9 days post infection (dpi) and caused severe necrotizing encephalitis with neurodegenerative changes in neurons, swelling and proliferation of vascular endothelial cells in the cerebral cortex, cerebellum, midbrain and brainstem. In contrast, infection with BTV serotypes 10 and 16 led to 25–30% mortality at 9–11 dpi and caused mild neuropathological lesions. BTV antigen was detected by immunohistochemistry, direct fluorescence antibody technique and confocal microscopy in the cytoplasm of neuronal cells of the hippocampus, grey matter of the cerebral cortex and vascular endothelial cells in the midbrain and brainstem of BTV-1, -2, -10, -16 and -23 infected groups from 3 to 20 dpi. BTV nucleic acid was detected in the infected brain tissues from as early as 24 h up to 20 dpi by VP7 gene segment-based one-step reverse transcriptase polymerase chain reaction. This study of the relative neurovirulence of BTV serotypes is likely to help design suitable vaccination and control strategies for the disease.